Toxicity and Damage Potential of Atmospheric Mercury Emissions from the Cement Industry in Japan - H. Habuer (Chemical Engineering Transactions)
Japan has made considerable efforts to minimise mercury use in products and manufacturing processes. Even if Japan emits less mercury into the atmosphere than other countries or regions, its potential toxicity to human health and ecosystems through long-term transport and accumulation remains unknown. Furthermore, there are opportunities to further reduce emissions, especially from large sources like cement plants. The lack of evaluations of the environmental burden of mercury from the perspective of its life cycle has led to observations of anthropogenic sources in Japan. This study compared atmospheric mercury emissions by the cement industry before and after the Minamata Convention on Mercury (hereafter called “Convention”) from 2014 to 2020 and explored the time-series human and ecosystem toxicity potentials. The atmospheric mercury emissions from cement production were essentially unchanged during 2014–2018, at around 5.5 t/y. They decreased dramatically to 4.5 t in 2019 and 3.2 t in 2020. Since 2019, the ecosystem, carcinogenic and non-carcinogenic human toxicity impacts of mercury have decreased; the toxicity potential in 2020 was 58.2 % of that in 2014. The potential damage to humans in Japan contributed 9.41 disability-adjusted loss of life years (DALY) to the world population in 2020, which equalled 0.00004 % of the impact of malaria on human health and 0.00002 % of that of traffic accidents. The harm to ecosystem diversity was 0.025 species lost in 2020. The framework of this study is valuable as a systematic evaluation of the effectiveness of strategic mercury management in countries facing similar problems.